The Influence of Digital Leadership and Organizational Commitment on Business Performance in Engineering SMES in Karawang - Nandang, Nandang; Jamaludin, Asep; Wanta, Wanta (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine the effect of digital leadership and organizational commitment on business performance in engineering MSMEs in Karawang. The locus of this research is the Karawang Engineering Entrepreneurs Association (APEK) with a population of 113 and the sample to be used is 88. This research method is quantitative with the analysis used is multiple linear regression. The results showed that digital leadership and organizational commitment have a positive and significant influence on the business performance of engineering MSMEs in Karawang. Leaders who optimize digital technology are able to improve efficiency, innovation and decision making, while strong employee commitment encourages productivity and loyalty. Simultaneously, both factors play an important role in creating a competitive and sustainable business environment. The implications of this research emphasize the importance of developing digital skills for MSME leaders, increasing organizational commitment and the need for policies that support digital transformation for MSMEs.